Mechanical Behavior of Elastic Self-Locking Nails for Intramedullary Fracture Fixation: A Numerical Analysis of Innovative Nail Designs - Putame, Giovanni; Pascoletti, Giulia; Terzini, Mara; Zanetti, Elisabetta M.; Audenino, Alberto L. (Frontiers in Bioengineering and Biotechnology, 2020)
Intramedullary nails constitute a viable alternative to extramedullary fixation devices; their use is growing in recent years, especially with reference to self-locking nails. Different designs are available, and it is not trivial to foresee the respective in vivo performances and to provide clinical indications in relation to the type of bone and fracture. In this work a numerical methodology was set up and validated in order to compare the mechanical behaviour of two new nailing device concepts with one already used in clinic. In detail, three different nails were studied: (1) the Marchetti-Vicenzi’s nail (MV1), (2) a revised concept of this device (MV2), and (3) a new Terzini-Putame’s nail (TP) concept. Firstly, the mechanical behaviour of the MV1 device was assessed through experimental loading tests employing a 3D-printed component aimed at reproducing the bone geometry, inside which the device is implanted. In the next step, the respective numerical model was created, based on a multibody approach including flexible parts, and this model was validated against the previously obtained experimental results. Finally, numerical models of the MV2 and TP concepts were implemented and compared with the MV1 nail, focusing the attention on the response of all devices to compression, tension, bending and torsion. A stability index (SI) was defined to quantify the mechanical stability provided to the nail-bone assembly by the elastic self-locking mechanism for the various loading conditions. In addition, results in terms of nail-bone assembly stiffness, computed from force/moment versus displacement/rotation curves, were presented and discussed. Findings revealed that numerical models were able to provide good estimates of load versus displacement curves. The TP nail concept proved to be able to generate a significantly higher SI (27 N for MV1 versus 380 N for TP) and a greater stiffening action (up to a stiffness difference for bending load that ranges from 370 Nmm/° for MV1 to 1532 Nmm/° for TP) than the other two devices which showed similar performances. On the whole, a demonstration was given of information which can be obtained from numerical simulations of expandable fixation devices.